HUBUNGAN ANTARA IQ, MOTIVASI BELAJAR DAN SIKAP TERHADAP DOSEN DENGAN PRESTASI BELAJAR PADA MATA KULIAH PSIKODIAGNOSTIKA 1 - Rezha Pustaka NZ; N. Kardinah; Witrin Gamayanti (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2012)
This research study about low achievement of psychology students academic year 2008 in psychodiagnostic 1 class. Based on interview, students have low achievement because of many factors such as learning motivation, attitude toward lectures, and intelegence level. Population are students at psychology faculty of UIN Sunan Gunung registered in academic year 2008 and taking psychodiagnostic 1 class. “Simple random sampling” represent population. Research design used partial correlation. Result shows that correlation between IQ, learning motivation and attitude toward lecturer is r = 0,551. It is concluded that correlation between those variables is significant. Correlation values from each variables are 0,478 for IQ, 0,029 for learning motivation and 0,268 for attitude towardlectures.